Prospects for the use of synthetic organoselenium compounds for the correction of metabolic and immune status during vaccination with live attenuated vaccines against especially dangerous infections - O. V. Yurieva; V. I. Dubrovina; A. B. Pyatidesyatnikova (Acta Biomedica Scientifica, 2021)
This review article analyzes the data on the role of selenium in the regulation of the metabolic and immune status of a macroorganism. The data on endogenousfunctional selenium-containing molecules, which include selenocysteine, selenomethionine, and selenoproteins, are considered. The data on the pathologies associated with the deficiency of this microelement, its  immunotropic properties and adjuvant effects are presented. The role of selenoproteins in the regulation of redox processes has been shown. The data on the immunotropic activity of compounds containing selenium and the prospects for their use as adjuvants are analyzed. The last section is devoted to the analysis of literature data on the biological properties of synthetic selenium compounds with an activity that mimics the catalytic activity of selenoproteins. The analysis of the data on the functional activity of selenoproteins carried out in this work indicates their key role in the regulation of metabolic and immune processes, as well as in maintaining homeostasis. The information presented in this review on the biological activity and mechanisms of action of new synthetic low-toxic organic compounds of selenium can serve as a basis for the development of nonspecific means of metabolic and immune correction of vaccinal processes caused by both live attenuated vaccines and artificially created ones.